การพัฒนารูปแบบการจัดการเรียนรู้ศิลปะเพื่อส่งเสริมทักษะการเรียนรู้แบบร่วมมือของนักเรียนในห้องเรียนรวมระดับชั้นประถมศึกษาตอนต้น; DEVELOPMENT OF ART LEARNING MANAGEMENT MODEL TO PROMOTE COOPERATIVE LEARNING SKILLS OF STUDENTS IN INCLUSIVE CLASSROOMS OF LOWER ELEMENTARY SCHOOL - (Nattakarn Anantrawan), ณัฎฐกาญจน์ อนันทราวัน; (Khanobbhorn Sangvanich), ขนบพร แสงวณิช; (Shotiga Pasiphol), โชติกา ภาษีผล (Journal of Education and Innovation, 2018)
การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อพัฒนารูปแบบการจัดการเรียนรู้ศิลปะเพื่อส่งเสริมทักษะการเรียนรู้แบบร่วมมือของนักเรียนในห้องเรียนรวมระดับชั้นประถมศึกษาตอนต้น โดยบทความนี้นำเสนอกระบวนการวิจัยและพัฒนา ใน 2 ระยะแรก คือ ระยะที่ 1 เป็นการศึกษาสภาพทั่วไปและแนวทางการจัดการเรียนรู้ศิลปะเพื่อส่งเสริมทักษะการเรียนรู้แบบร่วมมือในห้องเรียนรวมระดับชั้นประถมศึกษาตอนต้น ด้วยการสัมภาษณ์ผู้เชี่ยวชาญ จำนวน 15 คน และสังเกตการจัดการเรียนรู้ศิลปะในห้องเรียนรวมระดับชั้นประถมศึกษาตอนต้น จำนวน 5 โรงเรียน ส่วนระยะที่ 2 เป็นการสร้างรูปแบบการจัดการเรียนรู้และตรวจสอบคุณภาพด้วยการสนทนากลุ่มโดยผู้ทรงคุณวุฒิ และวิเคราะห์ข้อมูลเชิงคุณภาพด้วยการวิเคราะห์เนื้อหา ซึ่งสรุปได้ว่ารูปแบบการจัดการเรียนรู้มีความสอดคล้องกับทฤษฎีที่เกี่ยวข้องและเหมาะสมในการนำไปใช้ ผลการวิจัย พบว่า 1. การจัดการเรียนรู้ศิลปะในห้องเรียนรวมไม่ได้เน้นทักษะการเรียนรู้แบบร่วมมือและครูศิลปะยังขาดความเข้าใจเกี่ยวกับการจัดการเรียนรวม ซึ่งแนวทางการจัดการเรียนรู้คือครูศิลปะต้องการวางแผนการสอน เตรียมนักเรียน เตรียมสื่อวัสดุอุปกรณ์ และเตรียมสภาพแวดล้อมเพื่อให้เกิดการเรียนรู้แบบร่วมมือ 2. รูปแบบการจัดการเรียนรู้ประกอบด้วย 8 องค์ประกอบ โดย กระบวนการจัดการเรียนรู้มี 6 ขั้น คือ 1) วิเคราะห์ความสามารถทางศิลปะและจัดกลุ่ม 2) การรับรู้ทางศิลปะและสร้างสรรค์งานศิลปะตามธรรมชาติของแต่ละบุคคล 3) แบ่งปันประสบการณ์ทางศิลปะ 4) ร่วมมือสร้างสรรค์งานศิลปะ 5) ตรวจสอบพฤติกรรมการร่วมมือสร้างสรรค์งานศิลปะและให้ข้อมูลย้อนกลับ 6) แสดงผลงานและวิเคราะห์ผลการร่วมมือสร้างสรรค์งานศิลปะ DEVELOPMENT OF ART LEARNING MANAGEMENT MODEL TO PROMOTE COOPERATIVE LEARNING SKILLS OF STUDENTS IN INCLUSIVE CLASSROOMS OF LOWER ELEMENTARY SCHOOL The development of art learning management model to enhance cooperative learning skills of students in inclusive classroom of lower elementary school students has been aimed in this research. For this article presented the first two phases of research and development methodology, the first phase was to identifying situation and study guidelines of art learning management to enhance cooperative learning skills of students in inclusive classroom of lower elementary school students. By interview 15 experts and observation 5 of teaching art in inclusive classroom of lower elementary school. Phase 2 were to constructing the art learning management model and verifying the art learning management model quality with concurrence of the experts by focus group and content analysis. It was concluding that the Model was consistent with the Implicated theory and proper implementation. The result showed that; 1. Art learning management in inclusive classroom did not focus on cooperative learning skills and art teachers also lack of understanding about inclusive education. The guidelines of art learning management to enhance cooperative learning skills of students in inclusive classroom of lower elementary school students was art teacher need to; prepare lesson plan, prepare students, prepare media and materials, and prepare the environment to facilitate the students to learning together. 2. Art learning management model consisting of eight Elements, the learning process has six stages; 1) artistic capabilities analysis and grouping, 2) individual of art perception and creating artwork naturally, 3) shared artistic experience, 4) cooperative creating artwork, 5) monitoring actions of cooperative creating artwork and feedback, and 6) exhibit artwork and analyze the results of cooperative creating artwork.